(untitled) (Journal of Economic Research & Business Administration, 2016)
Currently, investment and innovation processes carried out in Kazakh stan, as the basic premises of socio – economic development, are the root cause of the successful implementation of reforms in the country.The new strategy of development of Kazakhstan till 2050 provides for the establish ment of priority conditions for the development of competitive economy, social policy, industrial hightech sector.Here, the main task – not only to attract money into the country, and the involvement of technology, and secondly, is now characterized by the formula «the exchange of raw ma terials technology». An innovative economy is built through the creation of new markets. Ideas in new markets, development, intellectual property, product innova tion replaces the old structure of the economy and transferred to a new quality.